A Demand-Driven Design for Irrigation in Egypt : Minimizing Risks for Both Farmers and Private Investors - Baietti, Aldo; Abdel-Dayem, Safwat (World Bank, Washington, DC, 2012)
A new type of irrigation project, designed for the West Delta region of the Arab Republic of Egypt, promises to usher in an era of cost recovery and sustainable operation and maintenance. The project, which emphasizes involving private investors and the farming community, deploys several innovative mechanisms, such as a strategy to mitigate demand, commercial, and currency risks. Unlike the centrally planned projects of the past, this one is demand driven. The focus is on developing an irrigation network with features that farmers want and are willing to pay for.